Self-efficacy and positive coping mediate the relationship between social support and resilience in patients undergoing lung cancer treatment: A cross-sectional study - Yin, Yizhen; Lyu, Mengmeng; Chen, Yiping; Zhang, Jie; Li, Hui; Li, Huiyuan; Xia, Guili; Zhang, Jingping (Frontiers in Psychology, 2022)
Background: The prognosis of patients undergoing lung cancer treatment might be influenced by mental health status. Resilience is one of the important predictors to reflect the mental health status. It has been shown that patients with higher levels of social support, self-care self-efficacy, and positive coping have greater resilience. This study aimed to determine the mediating role of self-efficacy and positive coping in the relationship between social support and psychological resilience in patients with lung cancer. Method: This is a cross-sectional study that was conducted in in the oncology departments and thoracic surgical wards of four tertiary hospitals in Hunan Province, China, between November 2016 and November 2017. Three hundred and three patients who were undergoing treatment for lung cancer volunteered their participation in the study. Participants completed questionnaires, including the Chinese version of the Perceived Social Support Seale Scale, the Chinese version of Strategies Used by People to Promote Health Scale, and the Chinese version of the Connor-Davidson Resilience Scale. Results: Mediation analysis indicated that self-care self-efficacy and social support partially mediate the effect of social support on resilience. Direct paths from social support to self-efficacy, self-efficacy to positive coping, positive coping to psychological resilience, self-efficacy to psychological resilience, and social support to psychological resilience were significant (p < 0.001). The indirect paths from social support to self-efficacy and self-efficacy to psychological resilience were also significant. The chain mediation from social support to self-efficacy, self-efficacy to positive coping, and positive coping to resilience were significant. Conclusions: Self-efficacy and positive coping play an important role in the relationship between social support and resilience in patients receiving cancer treatment. Social support not only directly influenced psychological resilience but also indirectly influenced psychological resilience through self-efficacy and positive coping.